Upaya Kepala Sekolah Menghadapi Dampak Negatif Era Disrupsi Siswa SMP Negeri Karang Jaya Kabupaten Musi Rawas Utara - Syaiful Bahri; Murni Yanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the principal's efforts to address the negative impacts of the disruptive era on students at Karang Jaya Public Junior High School in North Musi Rawas Regency. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The principal, vice principal, teachers, and students served as informants. The results indicate that the principal made various efforts, including establishing rules for technology use in schools, providing guidance to teachers, collaborating with parents or guardians, being aware of the latest innovations, utilizing educational technology, collaborating with the community, and instilling character values ​​in students. Challenges encountered included the difficulty of managing the school community and limited control over students outside the school environment. The study concluded that the principal's efforts were effective in minimizing the negative impacts of the disruptive era, although challenges in supervision and involvement of all parties remain obstacles that require attention. Keywords: Disruptive Era, Principal, Negative Impact, Educational Technology